Precisely Localized Bone Regeneration Mediated by Marine-Derived Microdroplets with Superior BMP-2 Binding Affinity - Jeon, Eun Young; Um, Seung-Hoon; Park, Jaeho; Jung, Youngmee; Cheon, Cheol-Hong; Jeon, Hojeong; Chung, Justin J. (Wiley - V C H Verlag GmbbH & Co., 2022)
Prompt and robust bone regeneration has been clinically achieved using supraphysiological doses of bone morphogenetic protein-2 (BMP-2) to overcome the short half-life and rapid clearance. However, uncontrolled burst release of exogenous BMP-2 causes severe complications such as heterotopic ossification and soft tissue inflammation. Therefore, numerous researches have focused on developing a new BMP-2 delivery system for a sustained release profile by immobilizing BMP-2 in various polymeric vehicles. Herein, to avoid denaturation of BMP-2 and enhance therapeutic action via localized delivery, a complex coacervate consisting of fucoidan, a marine-derived glycosaminoglycan, and poly-l-lysine (PLL) is fabricated. Superior BMP-2 binding ability and electrostatic interaction-driven engulfment enable facile and highly efficient microencapsulation of BMP-2. The microencapsulation ability of the coacervate significantly improves BMP-2 bioactivity and provides protection against antagonist and proteolysis, while allowing prolonged release. Moreover, BMP-2 containing coacervate is coated on conventional collagen sponges. The bioactivity and localized bone regenerating ability are confirmed through in vitro (human-derived stem cells), and in vivo (calvarial bone defect model) evaluations.